2016
DOI: 10.3389/fict.2016.00030
|View full text |Cite
|
Sign up to set email alerts
|

Making Tangible the Intangible: Hybridization of the Real and the Virtual to Enhance Learning of Abstract Phenomena

Abstract: Interactive systems based on augmented reality (AR) and tangible user interfaces (TUI) hold great promise for enhancing how to learn and understand abstract phenomena. In particular, they combine the advantages of numerical simulation and pedagogical support while keeping the learner involved in true physical experimentation. In this paper, we discuss three examples of such AR and TUI systems that address hardly perceivable concepts. The first example, Helios, targets K-12 learners in the field of astronomy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 79 publications
0
12
0
2
Order By: Relevance
“…That is to say, the rating qualities of a system must be rendered tangible to the respondents. As demonstrated/showed/illustrated in [13], a considerable number of reviews highlight the promise of TUIs. TUI has many advantages to improve interaction accessibility, building on everyday skills and experiences [60].…”
Section: Inspiration and Design Choicesmentioning
confidence: 96%
“…That is to say, the rating qualities of a system must be rendered tangible to the respondents. As demonstrated/showed/illustrated in [13], a considerable number of reviews highlight the promise of TUIs. TUI has many advantages to improve interaction accessibility, building on everyday skills and experiences [60].…”
Section: Inspiration and Design Choicesmentioning
confidence: 96%
“…They suggest that physical interactions (Naive Physics) have the potential to reduce the level of abstraction (extrinsic cognitive load) and facilitate learning through a more "intuitive" (meaning : facilitating through learning acquired since the user's early age) way to interact with the interface and its content [20]. This type of interface would also promote a more active engagement, through manual activities [20,39], allowing the learning of more complex, abstract or very intangible notions [12]. In line with [32], transferring interactions with the digital world into the real one could scaffold cognition, i.e.…”
Section: Learning and Reality-based Interactionmentioning
confidence: 99%
“…A first example of this association with didactic capabilities was presented by Underkoffler et al [35] where they used a video-projector to display on a tabletop a numerical simulation representing air flows that could be controlled by moving buildings miniatures. Later it was shown that this approach based on augmented physical manipulation can promote the understanding of complex and often abstract phenomena [12]. Still with the aim of facilitating the learning of complex concepts in a school context, Zufferey developed an augmented tabletop mixing SAR and TUI, called Tinker Lamp [40].…”
Section: Sar Tui Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Elles peuvent également s'appuyer sur des interfaces numériques de nouvelle génération modifiant les modalités d'interactions humain-machine, mais aussi entre leurs utilisateurs et avec les représentations des savoirs. C'est notamment le cas pour celles qui exploitent la réalité augmentée, les objets connectés, les robots et/ou les dispositifs tactiles ou tangibles (Cuendet et al, 2013;Fleck et Hachet, 2016, Schneider et al, 2011Kubicki et al, 2014). Ces interfaces de nouvelle génération en milieu scolaire, alternatives des écrans-clavier-souris, remettent en question les attentes, les besoins et les réalités de pratiques, non seulement des élèves mais aussi de leurs enseignants, et plus largement de toute la communauté éducative.…”
unclassified